Star Wars Episode III Revenge of the Sith - Lucas, George; Lucas, George; McCallum, Rick; McGregor, Ewan; Portman, Natalie; Christensen, Hayden; McDiarmid, Ian; Jackson, Samuel; Lee,Christopher (2005)
Torn between loyalty to his mentor, Obi-Wan Kenobi, and the seductive powers of the Sith, Anakin Skywalker ultimately turns his back on the Jedi. This begins his complete journey to the dark side and his transformation into Darth Vader.